Paradigmas y polifuncionalidad: Estudio diacrónico de «preciso»/«precisamente», «justo»/«justamente», «exacto»/«exactamente» y «cabal»/«cabalmente» - Gerhalter, Katharina (2020)
This book deals with the historical development of a group of four Spanish adjectives and adverbs: preciso / precisamente, justo / justamente, exacto / exactamente and cabal / cabalmente. Based on large historical corpus data-samples, this study combines quantitative and qualitative analysis with semasiological and onomasiological approaches and its focus lies on the diachronic development of three discourse functions (focussing, affirmation and reformulation). The results are discussed with reference to current theories of language change (grammaticalization, pragmaticalization, thetical grammar and cooptation) and explanatory factors such as analogy and changes in frequency.